Mini review: Multifaceted role played by cyclin D1 in tumor behavior - Reena Rachel John; N Malathi; C Ravindran; Soumya Anandan (Wolters Kluwer Medknow Publications, 2017)
The objective of this paper is to discuss and put forward the various diversified roles of cyclin D1 in cancer. Neoplasia is defined by abnormal regulation of the cell cycle. Cyclin D1 could be a protein derived from the PRAD1, CCND1, or bcl-1 sequence on body 11q13 that is concerned in each traditional regulation of the cell cycle and pathologic process. Within the G1 (resting) part of the cell cycle, cyclin D1 in conjunction with its cyclin-dependent enzyme (cyclin-dependent kinase) partner is accountable for transition to the S (DNA synthesis) part by phosphorylating the merchandise of the metastatic tumor sequence (protein retinoblastoma) that then releases transcription factors vital within the initiation of DNA replication. Amplification of the sequence or overexpression of the cyclin D1 releases a cell from its traditional controls and causes transformation to a malignant composition. Analysis of those changes provides vital diagnostic information in oral carcinogenesis and is of prognostic value in several cancers. Data of cyclin D1's role in malignancy at the assorted sites provide a basis on which future treatment directed against this molecule will proceed.